Focal scar and diffuse myocardial fibrosis are independent imaging markers in repaired tetralogy of Fallot. (16th April 2019) - Cochet, Hubert; Iriart, Xavier; Allain-Nicolaï, Antoine; Camaioni, Claudia; Sridi, Soumaya; Nivet, Hubert; Fournier, Emmanuelle; Dinet, Marie-Lou; Jalal, Zakaria; Laurent, Francois; Montaudon, Michel; Thambo, Jean-Benoît
Abstract: Aims: To identify the correlates of focal scar and diffuse fibrosis in patients with history of tetralogy of Fallot (TOF) repair. Methods and results: Consecutive patients with prior TOF repair underwent electrocardiogram, 24-h Holter, transthoracic echocardiography, exercise testing, and cardiac magnetic resonance (CMR) including cine imaging to assess ventricular volumes and ejection fraction, T1 mapping to assess left ventricular (LV) and right ventricular (RV) diffuse fibrosis, and free-breathing late gadolinium-enhanced imaging to quantify scar area at high spatial resolution. Structural imaging data were related to clinical characteristics and functional imaging markers. Cine and T1 mapping results were compared with 40 age- and sex-matched controls. One hundred and three patients were enrolled (age 28 ± 15 years, 36% women), including 36 with prior pulmonary valve replacement (PVR). Compared with controls, TOF showed lower LV ejection fraction (LVEF) and RV ejection fraction (RVEF), and higher RV volume, RV wall thickness, and native T1 and extracellular volume values on both ventricles. In TOF, scar area related to LVEF and RVEF, while LV and RV native T1 related to RV dilatation. On multivariable analysis, scar area and LV native T1 were independent correlates of ventricular arrhythmia, while RVEF was not. Patients with history of PVR showed larger scars on RV outflow tract but shorter LV and RV native T1. Conclusion: Focal scar and biventricular diffuse fibrosis can be characterized on CMR after TOF repair. Scar size relates to systolic dysfunction, and diffuse fibrosis to RV dilatation. Both independently relate to ventricular arrhythmias. The finding of shorter T1 after PVR suggests that diffuse fibrosis may reverse with therapy.